Obtenção e caracterização de dispersões sólidas do Tuberculostático isoniazida - SILVA, Anderson Pedrosa da (2023)
Isoniazid (ISO) is a drug used in the treatment of tuberculosis. It belongs to Class III of the biopharmaceutical classification system (BCS), with good water solubility and low membrane permeability. Nimesulide (NIM) is a non-steroidal anti-inflammatory drug (NSAID), belonging to BCS Class II, with low aqueous solubility and high membrane permeability. Obtaining solid drug dispersions (SDDs) has been a strategy to improve the physicochemical properties of drugs, such as water solubility. This study aimed to obtain and characterize new DSFs of ISO from the interaction with nimesulide (NIM) and malic acid (AML), through slow solvent evaporation (SSE). First, the molecular modeling of the starting compounds ISO, NIM and AML was carried out to study the possible interactions ISO-AML and NIM-ISO, through Density Functional Theory (DFT) with the functional ωB97X-D, the basis set 6-311++G(d,p) and the continuous solvation method IEFPCM using methanol. Subsequently, DSFs of ISO-AML and NIM-ISO were obtained by ELS, using methanol as solvent. Then, the samples were characterized by powder X- ray diffraction (PXRD); Fourier transform infrared spectroscopy (FT-IR); Raman spectroscopy (ER); thermogravimetry, derivative thermogravimetry, simultaneous differential thermal analysis (TG/DTG-DTA) and differential scanning calorimetry (DSC). The results of the molecular modeling for the starting compounds allowed the determination of the dipole moment, the energies of the HOMO and LUMO orbitals, as well as the reactivity indices and the electrostatic potential map (EPM), in each case, showing sites of probable interaction of the pyridine group of ISO with the carboxyl group of AML and sites of interaction of the nitro group of NIM with the pyridine group of ISO. PXRD results of ISO-AML binary mixtures at molar ratios of 1:2 and 1:3 showed typical diffraction profiles of amorphous materials, indicating the occurrence of intermolecular interactions between ISO and AML and the formation of solid dispersions of the type co- amorphous. The FT-IR and Raman analyzes of these co-amorphs confirmed this interaction through the clusters presented in the DFT. The DTA and DSC curves of these materials did not show melting events, confirming the amorphous nature of these solid dispersions. The TG/DTG curves showed that these materials showed good thermal stability up to 138.6 ºC. The results obtained by PXRD, by FT-IR and by Raman for the NIM-ISO binary mixtures investigated did not show the occurrence of intermolecular interactions between these compounds. However, the DTA and DSC curves of the NIM- ISO binary mixture (1:2) showed a single melting event around 132.0 ºC (Tonset), indicating the occurrence of physical interaction between these compounds and the formation of solid dispersions of the eutectic type. The TG-DTG curves of the eutectic NIM-ISO (1:2) showed that it was stable up to 184.0 ºC. The ISO SDDs obtained in this study are promising for the production of more effective drugs in the treatment of tuberculosis.